2003
DOI: 10.1016/s0019-1035(03)00205-7
|View full text |Cite
|
Sign up to set email alerts
|

A simple expression for vertical convective fluxes in planetary atmospheres

Abstract: We explore the vertical convective flux F c in a radiative-convective grey atmosphere. An expression of the form F c = F s τ o /(C + Dτ o ) appears useful, where F s is the shortwave flux absorbed at the base of an atmosphere with longwave optical depth τ o and C and D are constants. We find excellent agreement with an idealized grey radiative-convective model with no shortwave absorption for D = 1 and C = 1 ∼ 2 depending on the surface-atmosphere temperature contrast and on the imposed critical lapse rate. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…Using the numbers from above, this results in maximum theoretical work of about 83 000 TW. However, extracting work from this gradient competes with the radiative exchange, which also depletes this gradient, so a maximum power exists that can be extracted from this driver [48][49][50][51]37]. Following the same line of reasoning as in the last section, the simple model of Appendix B results in about 1/2 of the heat flux being able to be extracted to perform work at a maximum efficiency of 11.4%, yielding about 5000 TW.…”
Section: Solar Radiationmentioning
confidence: 86%
See 1 more Smart Citation
“…Using the numbers from above, this results in maximum theoretical work of about 83 000 TW. However, extracting work from this gradient competes with the radiative exchange, which also depletes this gradient, so a maximum power exists that can be extracted from this driver [48][49][50][51]37]. Following the same line of reasoning as in the last section, the simple model of Appendix B results in about 1/2 of the heat flux being able to be extracted to perform work at a maximum efficiency of 11.4%, yielding about 5000 TW.…”
Section: Solar Radiationmentioning
confidence: 86%
“…This was initially suggested by Edward Lorenz [70], and is closely related to the hypothesis formulated by Paltridge [71,13,72] that the atmospheric circulation maximizes entropy production. Since then, further work has shown that MEP yields reasonable predictions of hemispheric heat transport on other planetary bodies [14,73] and of empirical friction coefficients in atmospheric general circulation models [15,74], but also for vertical convection [71,75,49,37,51,76] and convection at hydrothermal vents at the seafloor [77]. More support comes from studies of turbulence and its effects on heat transport and entropy production [78][79][80][81][82].…”
Section: Maximizing Power Generation and Transfermentioning
confidence: 99%
“…The value obtained by MEP closely matched the empirical value used in the model. While Paltridge (1975) originally hypothesized maximum convective heat flux in the vertical, several authors have demonstrated that MEP is applicable to convection in the vertical as well (Ozawa and Ohmura 1997;Pujol and Fort 2002;Pujol 2003;Lorenz and Mckay 2003;Kleidon 2004a).…”
Section: Demonstration Of Mep States: Examplesmentioning
confidence: 99%
“…This principle was previously applied to poleward atmospheric heat transport and could reproduce temperature profiles on earth (Paltridge, 1975(Paltridge, , 1978, empirical values for turbulent dissipation (Kleidon et al, 2003, and the climate characteristics of other planets (Lorenz et al, 2001). It was applied to vertical exchange of radiation and heat within the atmosphere (Ozawa and Ohmura, 1997;Lorenz and Mckay, 2003;Kleidon, 2004) to determine vertical fluxes and resulting temperature profiles. The models developed here are very similar to those used in these studies, although the latent heat flux was not explicitly considered and the interpretation of the limit is different.…”
Section: Relation To Previous Workmentioning
confidence: 99%